Eye Tracking and the Museum Experience in Italy (Altre Modernità, 2020)
Understanding museum audiences and evaluating their experiences have long been at the core of theoretical and empirical research, from several disciplinary angles. Yet, a very limited amount of studies has, to date, resorted to eye tracking as a tool to map museum visitors' gazes, their preferences and also their difficulties in museum fruition. Eye tracking offers an objective window into audience perception and reception of a variety of stimuli, allowing the researcher to overcome many of the biases involved in qualitative empirical studies. This article presents the methodology used for two experiments carried out with eye tracking and other analytical tools at two different museums. It also focuses on the results obtained by the mixed-method investigations, with a view to promoting more systematic research into the museum experience with portable eye tracking technology.
Keywords: museum audience; eye tracking; media accessibility; reception studies; museum accessibility; audiovisual translation